2022
DOI: 10.3389/fcell.2022.966662
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction through adhesion molecules: Emerging roles in regulating the stem cell niche

Abstract: Stem cells have been shown to play an important role in regenerative medicine due to their proliferative and differentiation potential. The challenge, however, lies in regulating and controlling their potential for this purpose. Stem cells are regulated by growth factors as well as an array of biochemical and mechanical signals. While the role of biochemical signals and growth factors in regulating stem cell homeostasis is well explored, the role of mechanical signals has only just started to be investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 300 publications
(282 reference statements)
0
2
0
Order By: Relevance
“…This is consistent with several in vitro and in vivo studies which showed that the ECM composition (Battista et al ., 2005), stiffness (Urciuolo et al ., 2013), topography (Janson & Putnam, 2015) and the mechanical forces controlled by matrix adhesion (Guilak et al ., 2009) can regulate stem cell renewal and differentiation across various tissues. ECM-driven influences are thought to be mediated by intracellular mechano-sensing and transduction pathways involving a network of structural support proteins such as integrins, focal adhesions and the actin cytoskeletal network which are hypothesized to transduce changes to the nuclear envelope and influence the activity of transcription factors and chromatin remodelling enzymes (Lim et al ., 2022; Gattazzo et al ., 2014; Watt & Huck, 2013). Based on these and other studies, it can be hypothesized that FT stem cell maintenance is driven, at least in part, by cellular programmes that remodel the underlying ECM.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with several in vitro and in vivo studies which showed that the ECM composition (Battista et al ., 2005), stiffness (Urciuolo et al ., 2013), topography (Janson & Putnam, 2015) and the mechanical forces controlled by matrix adhesion (Guilak et al ., 2009) can regulate stem cell renewal and differentiation across various tissues. ECM-driven influences are thought to be mediated by intracellular mechano-sensing and transduction pathways involving a network of structural support proteins such as integrins, focal adhesions and the actin cytoskeletal network which are hypothesized to transduce changes to the nuclear envelope and influence the activity of transcription factors and chromatin remodelling enzymes (Lim et al ., 2022; Gattazzo et al ., 2014; Watt & Huck, 2013). Based on these and other studies, it can be hypothesized that FT stem cell maintenance is driven, at least in part, by cellular programmes that remodel the underlying ECM.…”
Section: Discussionmentioning
confidence: 99%
“…CAMs, such as integrins and pattern recognition receptors, act as mechanobiological sensors that identify and bind these ligands. When integrins bind to the ECM, they drive the assembly of focal adhesion complexes as well as the activation of integrin-associated protein kinases to initiate downstream signaling pathways for enhancing cell adhesion and survival [16,29,30]. Integrins bind ligands with lower affinity but at higher concentrations on cell surfaces, facilitating the formation of dense plaques upon activation, where multiple integrin molecules are anchored to cytoskeletal filaments to stabilize cell adhesion (Velcro principle) [31].…”
Section: Msc Adhesionmentioning
confidence: 99%